2012
DOI: 10.4049/jimmunol.1102686
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for Varied αβ TCR Usage against an Immunodominant EBV Antigen Restricted to a HLA-B8 Molecule

Abstract: EBV is a ubiquitous and persistent human pathogen, kept in check by the cytotoxic T cell response. In this study, we investigated how three TCRs, which differ in their T cell immunodominance hierarchies and gene usage, interact with the same EBV determinant (FLRGRAYGL), bound to the same Ag-presenting molecule, HLA-B8. We found that the three TCRs exhibit differing fine specificities for the viral Ag. Further, via structural and biophysical approaches, we demonstrated that the viral Ag provides the greatest en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 54 publications
(66 reference statements)
2
54
1
Order By: Relevance
“…To assess the effect of each mutation on the pMHC complex stability, a thermal shift assay was performed using fluorescent dye Sypro orange to monitor the protein unfolding as previously described (Gras et al, 2012). Results are reported in Supplemental Table 3.…”
Section: Thermal Stability Assaymentioning
confidence: 99%
“…To assess the effect of each mutation on the pMHC complex stability, a thermal shift assay was performed using fluorescent dye Sypro orange to monitor the protein unfolding as previously described (Gras et al, 2012). Results are reported in Supplemental Table 3.…”
Section: Thermal Stability Assaymentioning
confidence: 99%
“…Several structures of public TCRs in complex with pMHC have been reported: TCR JM22 bound to an influenza-derived peptide presented by HLA-A2 (22), TCRs bound to EBV-derived peptides presented by HLA-B8 (23)(24)(25)(26), and TCR RA14 bound to CMV NLV presented by HLA-A2 (27). In some cases these studies have identified unusual structural features of the selecting pMHC ligand, such as limited solvent accessibility or bulging of the viral peptide, which may explain the selection of dominant TCRs (22,23,26), whereas in other cases such features are not evident (24,25,27).…”
Section: Human Cytomegalovirus (Cmv)mentioning
confidence: 99%
“…This conformational alteration of Arg 62 also has been observed by others in two HLA-B8 structures (Fig. 5B) (37), one of which bound to a peptide with P1-Gly and its Arg 62 is at position 1, whereas in the other, the P1-Phe sterically forces the Arg 62 away to position 2 where it can engage and trigger various TCRs (38). Taking these previous findings into consideration, we hypothesized that in our structure, the acetyl moiety would provide a similar stereochemical effect as the phenyl group of Phe and that the Arg 62 at position 2 might contact with an incoming TCR.…”
mentioning
confidence: 77%